Variations of Arctic winter ozone from the LIMS Level 3 dataset - E. Remsberg; M. Natarajan; E. Hilsenrath (Atmospheric Measurement Techniques, 2022)
The Nimbus 7 Limb Infrared Monitor of the Stratosphere (LIMS) instrument operated from 25 October 1978 through 28 May 1979. Its Version 6 (V6) profiles and their Level 3 or zonal Fourier coefficient products have been characterized and archived in 2008 and in 2011, respectively. This paper focuses on the value and use of daily ozone maps from Level 3, based on a gridding of its zonal coefficients. We present maps of V6 ozone on pressure surfaces and compare them with several rocket-borne chemiluminescent ozone measurements that extend into the lower mesosphere. We illustrate how the synoptic maps of V6 ozone and temperature are an important aid in interpreting satellite limb-infrared emission versus local measurements, especially when they occur during dynamically active periods of Northern Hemisphere winter. A map sequence spanning the minor stratospheric warmings of late January and early February characterizes the evolution of a low-ozone pocket (LOP) at that time. We also present time series of the wintertime tertiary ozone maximum and its associated zonally varying temperatures in the upper mesosphere. These examples provide guidance to researchers for further exploratory analyses of the daily maps of middle atmosphere ozone from LIMS.